An Analysis of Illocutionary Acts in the Utterances of Detective Inspector Lestrade in SHERLOCK (BBC): A Study in Pink Movie - Iqbal Resmana; Kurniawan Kurniawan (IKIP Siliwangi, 2018)
This study has an aim to identify the kinds of speech act which are used in the utterances of Detective Inspector Gregory Lestrade, in Sherlock (BBC):A Study in Pink. In conducting this study, qualitative method is used to find the types of speech acts based on Searle’s theory in 1979, in the character’s utterances throughout the series. In presenting the data of the study, it is conducted by using descriptions. From the result of analysis, it is found that four out of five kinds of speech act are used by Lestrade, those are representatives, directives, commissives, and expressives. The findings also show that the representative speech act is the most dominant (53%) among the other three; meanwhile, expressive speech act is the least dominant (2.83%). Representative speech act, which functions for the speaker to state something they believe as the case or not reflects the role of Lestrade as a supporting character in the series that often gives Sherlock Holmes a lot of information about the cases and the clues for the case, also this is to fulfill his role as a Detective Inspector which could gather information from many sources and inform them to other people.